Penerapan Pendekatan Matematika Realistik Untuk Meningkatkan Kemampuan Komunikasi Matematis - Raden Sri Ayu Ramadhana; Defri Rahmat; Muhammad Fauzi Romadhon Marpaung (Departement of Mathematics Education, 2024)
This research aimed to find out: (1) the application of the Realistic Mathematics Education to improve students' mathematical communication skills and (2) the increase of students' mathematical communication abilities using the Realistic Mathematics Education. This is classroom action research used Kemmis and Taggart model design with four stages, namely Planning, Action, Observation and Reflection. The instruments used were tests of students' mathematical communication skills, questionnaires, observations and interviews. The research subjects were 36 students in class VIII grade of MTs Ar-Royyan. From data analysis, it was found that in cycle I students' mathematical communication skills reached 73.61% which meant achieving the level of classical learning completeness and in cycle II it was 86.11%. In other words, there was an increase in students' mathematical communication skills by applying the Realistic Mathematics Education.